2014
DOI: 10.1007/s10511-014-9310-4
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation Rates in Nearby Markarian Galaxies

Abstract: The star formation rates for the 230 nearest Markarian galaxies with radial velocities VLG <3500 km/s have been determined from their far ultraviolet fluxes obtained with the GALEX satellite. We briefly discuss the observed relationship between the star formation rate and other integral parameters of these galaxies: stellar mass, hydrogen mass, morphological type, and activity index. On the average, the Markarian galaxies have reserves of gas that are a factor of two smaller than those of galaxies in the field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
3
1
0
Order By: Relevance
“…We found that the fraction of AGN in paired samples is a little higher (but not significantly in the statistical sense) than in our isolated galaxy sample. We suggest that AGN phenomenon is not necessarily connected with environmental density and, most probably, defined by secular galaxy evolution confirming the previous results by Coziol et al (2011), Hernandez-Ibarra et al (2013, Karachentseva et al (2014) and Pulatova et al (2015).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that the fraction of AGN in paired samples is a little higher (but not significantly in the statistical sense) than in our isolated galaxy sample. We suggest that AGN phenomenon is not necessarily connected with environmental density and, most probably, defined by secular galaxy evolution confirming the previous results by Coziol et al (2011), Hernandez-Ibarra et al (2013, Karachentseva et al (2014) and Pulatova et al (2015).…”
Section: Discussionsupporting
confidence: 92%
“…In general, we are in agreement with the results obtained in previous works by other authors, see for example Peng et al (2010Peng et al ( , 2012 and Tal et al (2014). Karachentseva et al (2014) studied the SF R of the Markarian galaxies, which are active galaxies with different signs of activity (Markarian et al 1989, Mazzarella & Balzano 1986, Petrosian et al 2007): quasars, Seyfert galaxies, Wolf-Rayet, Starburst and HII galaxies. The authors found that SF R in Markarian galaxies is a little higher than in isolated galaxies, though the SSF R does not exceed a limit of ∼dex(- 9.4) [-yr −1 ], also noted in subsection 3.4 of this paper.…”
Section: Morphology Mass Sf R and Ssf R Comparisonsupporting
confidence: 93%
See 2 more Smart Citations